A novel internally hybrid absorption-compression heat pump for performance improvement. (15th July 2018) - Wu, Wei; You, Tian; Wang, Jian; Wang, Baolong; Shi, Wenxing; Li, Xianting
Highlights: New hybrid absorption-compression heat pumps are proposed for performance improvement. Single-effect and generator-absorber-heat-exchange hybrid heat pumps are considered. High absorption ratio yields higher heating efficiency but lower cooling efficiency. Hybrid heat pump can realize flexible heating/cooling capacity ratios as necessary. Hybrid heat pump with high absorption ratios well match the heating-dominant regions. Abstract: Heat pump technologies play significant roles in building energy saving and emission reduction. Combing the opposite characteristics of the electrical and absorption heat pumps, a novel internally hybrid absorption-compression heat pump was proposed for performance improvement. The thermodynamic models for the hybrid heat pump using two cycles (single-effect and generator-absorber-heat-exchange) were built for component design and performance simulation with various refrigerant distribution ratios. Results show that a higher absorption-side refrigerant ratio generally makes the primary energy efficiency less sensitive and the capacity more sensitive to working condition. In the heating mode, a higher absorption-side refrigerant ratio brings about a higher efficiency when the evaporator inlet temperature is below 16 °C and 20 °C for the two cycles. In the cooling mode, a lower absorption-side refrigerant ratio contributes to a higher efficiency. The hybrid absorption-compression heat pumps can realize flexible heating/cooling capacity ratios to accommodate the design heating/cooling loads as necessary. Generally, a higher absorption-side refrigerant ratio is preferred in colder conditions owing to the higher heating efficiency and the higher heating/cooling capacity ratio, well matching the heating-dominant building loads. This study focuses on the principle and performance of the novel hybrid heat pump, the applications in actual buildings will be conducted through year-round simulations in future studies.